Short-term surgical outcomes in patients with unilateral complete cleft lip and palate after presurgical nasoalveolar molding therapy: A three-dimensional anthropometric study - Yin, Jiayi; Zhang, Shiming; Huang, Ning; Shi, Bing; Zheng, Qian; Yang, Chao (Frontiers in Pediatrics, 2022)
Objective: This brief research report aimed to evaluate the short-term efficacy of presurgical nasoalveolar molding (PNAM) therapy on the nasolabial morphology three dimensionally in patients with non-syndromic complete unilateral cleft lip and palate (UCLP). Methods: Thirty-six patients with non-syndromic complete unilateral complete cleft lip and palate were enrolled retrospectively and categorized into 2 groups: 18 patients who had received PNAM treatment (PNAM group) and 18 age-matched patients who have not receive PNAM treatment (no PNAM group) from 2017 to 2021. The average starting age for PNAM therapy was 18.33 days, and the average PNAM treatment duration was 99.08 days. Twelve nasolabial parameters were measured to compare the postsurgical outcomes of two groups. Results: In PNAM groups, cleft width, vertical distance between double Crista philtri and columellar deviation were reduced compared to that in no PNAM group. And nostril height was larger than that in no PNAM group. The differences between two groups were statistically significant (p<.05). There were no statistical differences in columellar length, nostril width and bi-alar width between two groups. However, the nostril width on cleft side in PNAM group was decreased by an average of 1.1mm. Conclusion：Our result indicated that PNAM therapy decreased cleft width and vertical distance between Crista philtri. It also increased nasal symmetry by decreasing columellar deviation, increasing nostril height.